Barriers and facilitators to using the CommFit™ smart phone app to measure talk time for people with aphasia. Issue 8 (3rd August 2017) - Brandenburg, Caitlin; Worrall, Linda; Copland, David; Rodriguez, Amy D.
ABSTRACT: Background : The use of mobile technology in aphasia rehabilitation is an emerging area of research. CommFit™ is a smart phone application which was developed according to aphasia-friendly guidelines to measure the talk time of people with aphasia. Presently, the ease-of-use of CommFit™ for people with aphasia has not been investigated, and there is little research on the barriers and facilitators to using mobile technology for this population. Aims : The aim of this study was to describe the barriers and facilitators experienced by people with aphasia while using CommFit™. Methods & Procedures : Twelve people with aphasia used the CommFit™ system-app, iPhone and BlueTooth headset, to measure their talking time for 14 days. The Western Aphasia Battery-Revised Aphasia Quotient was used to determine aphasia severity. During the initial training session and data collection period, field notes were taken by researchers. At the end of the data-collection period, participants completed an ease-of-use rating scale and participated in semi-structured interviews on the barriers and facilitators to using the CommFit™ system. Outcomes & Results : Field notes and data from semi-structured interviews identified eight barriers; physical and language impairments related to stroke, other physical barriers not related to stroke, time constraints, unfamiliarity with technology, social attitudes, design of the technology and technology malfunction. Facilitators included support from researchers, support from other people, app design and use of the manual. On the ease-of-use rating scale, steps involving the headset were rated as less usable than other steps involved in using the CommFit™ system. However, all steps had mean scores indicating that they were "easy to use" or "very easy to use". Spearman correlations indicated that there was no significant relationship between ease-of-use ratings and aphasia severity. However, there was a significant negative correlation between age and ease-of-use rating of "pairing the headset" ( r = −0.8173, p = 0.013). Conclusions : The results of this study identified barriers to using mobile technology, many of which were not connected to the participants' stroke-related impairments. It also identified several facilitators which should be capitalised on when using mobile technology with this population. Last, results indicated that the BlueTooth headset was not a highly usable component of the CommFit™ system, especially for older users. This will be addressed in future research on the app.